The Effect of Ratio of Soursop (Annona muricata L.) with Beet Pulps (Beta vulgaris) and Arabic Gum Concentration on the Quality of Fruit Leather - Putri Septia Rini; Rona J. Nainggolan; Ridwansyah Ridwansyah (Jurnal Rekayasa Pangan dan Pertanian, 2016)
The aim of this research was to find the effect of ratio of soursop with beet pulps and several arabic gum concentration on the quality of mixture soursop and beet fruit leather. This research was conducted at the Laboratory of Food Technology, Faculty of Agriculture, University of Sumatera Utara, Medan, using completely randomized design with two factors, i.e. :ratio of  soursop with beet pulps (P) : (90% : 10% ; 80% : 20% ; 70% : 30% ; 60% : 40%; 50% : 50%) and arabic gum concentration (S): (0,8%, 1% and 1,2%). Parameters analyzed were moisture content, vitamin C content, total soluble solid, fiber content, total acid, ash content, score of  organoleptic values of colour, taste and texture and hedonic of organoleptic values of colour, taste, flavour and texture. The results showed that the ratio soursop with beet pulps the had highly significant effect on moisture content, vitamin C content, total soluble solid, fiber content, total acid, ash content, score of organoleptic values of colour, taste and texture, and hedonic of organoleptic values of colour, flavor, taste and texture. Arabic gum concentration had highly significant effect on moisture content, vitamin C content, total acid, ash content and score of organoleptic values of texture. Interactions of the two factors had highly significant effect on moisture content, vitamin C content, ash content and had no significant effect on total soluble solid, fiber content, total acid, score of organoleptic values of colour, taste and texture, and hedonic of organoleptic values of colour, flavor, taste and texture. The ratio of  soursop with beet pulps of (90% : 10%) and Arabic gum concentration of (1,2%) produced the best quality and more acceptable of fruit leather. Keywords: Arabic gum, Beet, Fruit leather, Soursop.